Analysis of Environmental Factors with Chronic Diarrhea in Toddlers in Jambi City in 2019 - Eko Misriyanto; Rico J. Sitorus; Misnaniarti (GoAcademica Research & Publishing, 2020)
Chronic diarrhea is defecation with a frequency of 3 or more times in infants and children lasting for 14 days. The impact of diarrheal disease in general causes loss of fluid in the body (dehydration) and chronic diarrhea can cause a child to experience poor nutritional status and experience growth failure. This study uses a case-control design using a retrospective approach. The number of samples in this study was 135 respondents. Instruments for collecting data in the form of questionnaires and observations. Data were analyzed by univariate, bivariate using the Chi-Square test, and multivariate analysis with multiple logistic regression. The statistical test results obtained p-value on the variables of clean water supply (0.007), latrine ownership (0.001), sewerage system (0.04), confidence degree 95% Confidence Interval (95% CI) and p-value ˂ 0, 05, it can be concluded that there is a significant relationship with chronic diarrheal disease in infants. The results of multiple logistic regression tests, on the variable wastewater discharge obtained OR = 3.801, meaning that sewerage is closely related to causing chronic diarrheal disease in infants.